XRD Investigation of Some Thermal Degraded Starch Based Materials. (5th December 2016) - Todica, Mihai; Nagy, Elena Mihaela; Niculaescu, Carmen; Stan, Oana; Cioica, Nicolae; Pop, Cornel Viorel
Abstract : The thermal degradation of some starch based materials was investigated using XRD method. The samples were obtained by thermal extrusion of mixtures of different proportions of starch, glycerol, and water. Such materials are suitable for the manufacturing of low pollutant packaging. Thermal degradation is one of the simplest ways to destroy such materials and this process is followed by structural modification of the local ordering of samples, water evaporation, crystallization, oxidation, or destruction of the chemical bonds. These modifications need to be studied in order to reduce to the minimum production of pollutant residues by burning process. XRD measurements show modification of the local ordering of the starch molecules depending on the temperature and initial composition of the samples. The molecular ordering perturbation is more pronounced in samples with low content of starch.